2009
DOI: 10.1007/s10705-009-9309-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management in organic farming: comparison of crop rotation residual effects on yields, N leaching and soil conditions

Abstract: After 3 years of different crop rotations in an organic farming experiment on a sandy soil in northwest Germany, spring triticale was cultivated on all plots in the fourth year to investigate residual effects on yield, nitrogen (N) leaching and nutrient status in the soil. Previous crop rotations differed in the way N was supplied, either by farmyard manure (FYM, 100 and 200 kg N ha -1 year -1 ) or by arable legumes like grass-red clover and field beans, or as a control with no N. Other crops in the rotations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
5
21
0
Order By: Relevance
“…Previous reviews have compared the net N 2 O emissions and NO 3 leaching from these systems. Lower areascaled, but roughly similar yield-scaled emissions (slightly higher, similar or slightly lower) are commonly observed for N 2 O emissions (Tuomisto et al, 2012;Skinner et al, 2014Skinner et al, , 2019 and NO 3 leaching (Kirchmann and Bergström, 2001;Stopes et al, 2002;Aronsson et al, 2007;Tuomisto et al, 2012;Benoit et al, 2014) from organic versus non-organic arable crop production.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous reviews have compared the net N 2 O emissions and NO 3 leaching from these systems. Lower areascaled, but roughly similar yield-scaled emissions (slightly higher, similar or slightly lower) are commonly observed for N 2 O emissions (Tuomisto et al, 2012;Skinner et al, 2014Skinner et al, , 2019 and NO 3 leaching (Kirchmann and Bergström, 2001;Stopes et al, 2002;Aronsson et al, 2007;Tuomisto et al, 2012;Benoit et al, 2014) from organic versus non-organic arable crop production.…”
Section: Introductionsupporting
confidence: 59%
“…On average over 3 years on loamy sand in Denmark, De Notaris et al (2018) reported NO 3 leaching that was about twice as high following a barley-pea intercrop compared with spring wheat or spring barley. In a sandy soil in northwestern Germany, Kayser et al (2010) observed that 83 kg N ha −1 leached in triticale following field bean. In a worst-case scenario, Askegaard et al (2011) observed annual NO 3 leaching of 270 kg N ha −1 during and after a lupin crop on a course sandy soil in a situation where the lupin crop did not ripen, leaving a large amount of N in crop residues (same experiment as De Notaris et al, 2018).…”
Section: Grain Legumesmentioning
confidence: 98%
See 2 more Smart Citations
“…This study also demonstrate positive effects that a shortterm (5 year) pasture can have on soil organic matter quantity and quality and its attendant benefits on soil N mineralization and soil structure. Farmyard manure application and returning leguminous crop residue to the field can increase the soil organic nitrogen mineralization and leaching risk (Kayser et al 2010). Fertilization of mid-rotation in Pinus radiata plantations makes unexpected sustained growth responses for more than 6 years and volume gains of 25m 3 ha -1 and 50m 3 ha -1 in sandy and granitic soil.…”
Section: Discussionmentioning
confidence: 99%